From Personality to Performance: The Mediating Role of Creativity in Behavioral Management Accounting Systems - Watti, Risa; Dihardjo, Djojo (University Merdeka Malang, 2026)
This study examines the influence of Big Five personality traits on member performance, with creativity as a mediating mechanism, from a behavioral management accounting perspective. While prior research links personality and performance, limited evidence exists in non-profit community settings emphasizing non-financial performance measurement. Using survey data collected from active members of a community-based organization in Surabaya, this study applies Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the proposed relationships. The findings indicate that Big Five personality traits significantly influence creativity, which in turn positively affects member performance. Personality also demonstrates a direct effect on performance. Creativity partially mediates the relationship between personality and non-financial performance. These results highlight the importance of behavioral factors in strengthening management control systems and improving non-financial performance outcomes. The study contributes to behavioral management accounting literature by integrating personality and creativity within a community organization context.